PENINGKATAN AKTIVITAS BELAJAR SISWA MELALUI METODE PICTURE AND PICTURE - Daswati Daswati (Journal of Education on Social Science (JESS), 2020)
Based on the experience and observation of the author about the condition in SMP Negeri 2 Pariangan class VII 1 in the school year 2016 – 2017, students seemed less involved in the learning process. This was because the method of learning used by teachers that have not varied so as not interesting for students. This study aimed to determine whether the use of picture and picture method could improve student learning activities in class VII.1 SMPN 2 Pariangan Tanah Datar. This research was conducted through Classroom Action Research which was conducted in 2 cycles. The results of this study indicated that the use of Picture and Picture method was able to improve student learning activities. This could be seen from the average of student activity reaching 84% in learning which previously only at 52%.